2017
DOI: 10.3390/ma10101119
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Mechanisms of Dodecylbenzene Sulfonic Acid by Corn Straw and Poplar Leaf Biochars

Abstract: Biochar is an eco-friendly, renewable, and cost-effective material that can be used as an adsorbent for the remediation of contaminated environments. In this paper, two types of biochar were prepared through corn straw and poplar leaf pyrolysis at 300 °C and 700 °C (C300, C700, P300, P700). Brunaer–Emmett–Teller N2 surface area, scanning electron microscope, elemental analysis, and infrared spectra were used to characterize their structures. These biochars were then used as adsorbents for the adsorption of dod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 40 publications
1
6
2
Order By: Relevance
“…Therefore, the physical adsorption mainly comprises surface adsorption (contact adsorption, similar to gravitational interaction between the mass objects), intraparticle diffusion, and electrostatic interaction for NO 3 − and NH 4 + adsorption on JB. This can be clearly observed in the SEM data collected after adsorption ( Figure 11 ), and is widely accepted by the scholars [ 14 , 41 , 42 ]. As shown in Figure 11 , the pores of the JB surface are filled with adsorbed NO 3 − and NH 4 + , and a white residue is also present inside the pores.…”
Section: Resultssupporting
confidence: 62%
“…Therefore, the physical adsorption mainly comprises surface adsorption (contact adsorption, similar to gravitational interaction between the mass objects), intraparticle diffusion, and electrostatic interaction for NO 3 − and NH 4 + adsorption on JB. This can be clearly observed in the SEM data collected after adsorption ( Figure 11 ), and is widely accepted by the scholars [ 14 , 41 , 42 ]. As shown in Figure 11 , the pores of the JB surface are filled with adsorbed NO 3 − and NH 4 + , and a white residue is also present inside the pores.…”
Section: Resultssupporting
confidence: 62%
“…The high temperature pyrolysis is generally the most common and important carbonization method [ 9 ]. Under limited oxygen supply or anoxic conditions and at a certain temperature (<700 °C), biomass resources can be carbonized into biochar, a carbon-rich, stable, and highly aromatic solid product [ 10 , 11 , 12 , 13 ]. At present, because of its large specific surface area, high stability, strong adsorption capacity, porous structure, as well as its wide range of raw materials, and low cost, biochar was widely used in agricultural and environmental protection fields such as pollution remediation, modified materials, soil improvement, etc., [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overall yield and selectivity of the two combined steps for the production of biodegradable and renewable anionic surfactants with the different fatty alcohols (C 8 -C 18 ) were very high (Table 2), which demonstrated the high efficiency and sustainability of the developed catalytic process. Measurements of the surface tension in water solutions of these surfactants showed that 5-(octadecyloxymethyl)-2-furoic acid sodium salt (SODF) had a similar surface tension (35 m Nm À 1 ) as the commercial dodecylbenzene sulfonic acid sodium salt (SDBS) (33 m Nm À 1 ) for 1 wt% concentration in water, although the CMC for SODF was 0.9 g g À 1 while reported CMC [49] for SDBS was 0.413 g L À 1 . [48]…”
Section: Chemsuschemmentioning
confidence: 99%